Association Between Procalcitonin and Post-hepatectomy Liver Failure in Hepatocellular Carcinoma Patients - Li, Yi-Ran; Meng, Xiao-Yan; Zong, Rui-Qing; Wu, Fei-Xiang (Frontiers in Pharmacology, 2021)
Objectives Procalcitonin (PCT) has long been proved as an early diagnostic signal for postoperative outcomes. The purpose of this study is to explore the value of serum procalcitonin levels in predicting post-hepatectomy liver failure (PHLF), and further to declarethe relationship between postoperative PCT and short-term prognosis in patients after hepatectomy. Methods Clinical data of patients with hepatocellular carcinoma (HCC) who underwent hepatectomy from June 1st, 2019 to September 31st, 2020 at Shanghai Eastern Hepatobiliary Surgery Hospital had been retrospectively analyzed. Logistic regression analysis was used to evaluate the risk factors related to PHLF. The Kaplan-Meier method was used to calculate the PHLF rate and 30-day survival after surgery. ResultsA total of 885 patients with complete data were finally included in analysis, 311 of them with elevated serum PCT (≥1ng/mL). Results of the logistic regression analysis suggested a significant association between PCT and PHLF [HR, 95%CI; 3.801 (1.825, 7.917), P<0.001]. Other significant risk factors for PHLF included portal hypertension, portal blocking time (>30min) and blood transfusion (>200ml). Kaplan-Meier analysis also suggested a higher PHLF rate in elevated PCT patients [9.0% (95% CI, 7.3 to 12.8 VS. 1.9% (95% CI, 1.1 to 4.3)); P<0.001]. For secondary outcomes, elevated PCT was also highly associated with postoperative sepsis, ICU admission, 30-day mortality and 3-month mortality. Conclusion: Elevated procalcitonin level in patients after hepatectomy is related to higher PHLF rate, with lower 30-day survival and poor short-term postoperative outcomes.